2004
DOI: 10.1080/15287390490492377
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Taste and Odor: A Primary Signal of Drinking-Water Integrity

Abstract: Aquatic taste and odor (T/O) is rarely produced by toxic contaminants or pathogens; nevertheless, it has major negative impacts on the public and the drinking-water industry. Consumers use T/O as a primary measure of drinking water safety, yet this criterion is poorly understood, and its origins and triggers often go untraced. Much surface-water T/O is produced by the increased production of volatile organic compounds (VOCs) by algae. These chemicals can be symptomatic of short-term problems with source, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(121 citation statements)
references
References 71 publications
(87 reference statements)
1
113
0
7
Order By: Relevance
“…And, the species responsible for the production of geosmin needs further study. The aldehyde compounds, including hexanal, heptanal, nonanal and decanal, were mainly associated with algal metabolites (Yasuhara and Fuwa, 1982;Watson, 2004;Zhang et al, 2013).…”
Section: Odorant Removal In Wtpmentioning
confidence: 99%
See 2 more Smart Citations
“…And, the species responsible for the production of geosmin needs further study. The aldehyde compounds, including hexanal, heptanal, nonanal and decanal, were mainly associated with algal metabolites (Yasuhara and Fuwa, 1982;Watson, 2004;Zhang et al, 2013).…”
Section: Odorant Removal In Wtpmentioning
confidence: 99%
“…Several nitrogen containing compounds including pyrazine, tetramethyl-pyrazine, pyridine, thiazole and 2-nitro-phenol, which may be associated with the stinky/fishy/sour/medicinal like odors (Watson, 2004) example, Pandey reported that pyridine was detected in waste gas emissions with unpleasant fishy odor (Pandey et al, 2007). Thiazole was an important flavor compound in food fields with unpleasant smell (Mahattanatawee et al, 2007).…”
Section: Odorant Removal In Wtpmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile organic compounds (VOCs), one contaminant group of concern, could be originated from photochemical and microbial activities (Fink, 2007;Watson, 2004) and introduced to the aquatic environment by emission and combustion (Liu and Zhou, 2011). Halogenated hydrocarbons used to be thought as the most frequently detected VOCs, followed by benzene, toluene, ethylbenzene and xylene (Chary and FernandezAlba, 2012;Ma et al, 2014), thus they were known as common VOCs (Niri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chrysophyta, Cryptophyta, and diatoms were the dominant algae during winter. Some members in these phyla, including Dinobryon, Cryptomonas, Asterionella, Melosira, Synedra, and Cyclotella, reportedly contain high intracellular unsaturated and polyunsaturated fatty acids associated with fishy/oily/cucumber odors in water (Watson, 2004). It could be speculated that the fishy odors in the Yellow River might be associated with the presence of these species.…”
Section: Odor Characteristicsmentioning
confidence: 99%